Determinan Pressure, Opportunity, Rationalization, Gender, dan Religiusitas terhadap Kecurangan Akademik pada saat Pembelajaran Hybrid - Asma, Adelia; Biduri, Sarwenda (Innovative Technologica: Methodical Research Journal, 2023)
Academic cheating is an increasing problem in hybrid learning. Studies that focus on the factors that cause academic cheating have been carried out, but the research results are inconsistent. The aim of the study is to find the consistency of the factors that influence academic cheating, especially the fraud triangle. This research method uses a quantitative approach. Partial t-test data analysis technique is used to test hypotheses on IBM SPSS software version 26. The research subjects were accounting students at the Muhammadiyah University of Sidoarjo class of 2018, totaling 73 respondents. In determining the research sample, this study used simple random sampling technique and the number of samples is determined with Slovin formula. This study shows the variables that influence, namely the opportunity, rationalization, and religiosity variables that affect academic cheating during hybrid learning. Meanwhile, pressure and gender variables have no effect on academic cheating during hybrid learning.